PELAKSANAAN SUPERVISI AKADEMIK OLEH KEPALA SEKOLAH UNTUK MENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM PENYUSUNAN PERENCANAAN PEMBELAJARAN - Yandri Yandri (Jurnal Muara Olahraga, 2021)
ABSTRACT: This study aims to help improve the pedagogical competence of teachers at SMP Negeri 7 Tanah Sepenggal in preparing lesson plans that are in accordance with the competency standards of each lesson so that they can become a reference in the learning process. This research was conducted in three stages, namely preparation, implementation and evaluation and reflection, and was carried out in at least two cycles. In the preparation stage, scenarios of activities, time schedules, places, and other supporting facilities are made, such as observation sheets and questionnaires. This study was aimed at all 5 subject teachers, namely Social Sciences, ICT, Science, Civics, and Physical Education subject teachers. This research was conducted in three stages, namely preparation, implementation and evaluation and reflection, and was carried out in at least two cycles. In the preparation stage, scenarios of activities, time schedules, places, and other supporting facilities are made, such as observation sheets and questionnaires The results showed that in the component of the formulation of the learning objectives indicators, there was an increase from 40% in the initial ability, to 60% in cycle 1 and increased to 70% at the end of the activity. The component of strategy selection and learning methods, which includes learning steps and determining the time allocation used, shows a significant increase from 40% to 60% in cycle 1 and again to 75% after cycle 2. Keywords: supervision, pedagogy, lesson planning